HACKED: DEFINING THE 2016 PRESIDENTIAL ELECTION IN THE LIBERAL MEDIA. - JUSTICE, JACOB W.; BRICKER, BRETT J. (Rhetoric & Public Affairs)
Despite consensus that Russia's interference in the 2016 election did not extend to actual hacking of voting technology, Russian efforts to intervene on behalf of the Trump campaign have been defıned as "hacking" by elements of the liberal media. This defınition is broadly accepted in liberal circles, and there is now a widespread misperception that Russia tampered with voting technology to alter the outcome of the election. In this essay, we trace the emergence of this defınition of Russia's role in the 2016 election and explain the factors that led to its acceptance, arguing that the debate over Russia's "hacking" illustrates that defınitional arguments may operate differently than scholars have previously conceived. Traditional studies of defınition emphasize the role of political leaders in crafting salient defınitions, adopting a top-down approach. We argue that defınitions also emerge from the bottom up, moving from media sources toward institutional centers of power. Our fındings both illustrate the dangers of efforts to defıne Russia's influence campaign as "hacking" and extend previous scholarship on defınitional argument.